A note on the geometric ergodicity of a nonlinear AR-ARCH model - Mika Meitz; Pentti Saikkonen (TÜSİAD-Koç University Economic Research Forum, 2010)
This note studies the geometric ergodicity of nonlinear autoregressive models with conditionally heteroskedastic errors. A nonlinear autoregression of order p (AR(p)) with the conditional variance specified as the conventional linear autoregressive conditional heteroskedasticity model of order q (ARCH(q)) is considered. Conditions under which the Markov chain representation of this nonlinear AR-ARCH model is geometrically ergodic and has moments of known order are provided. The obtained results complement those of Liebscher [Journal of Time Series Analysis, 26 (2005), 669-689] by showing how his approach based on the concept of the joint spectral radius of a set of matrices can be extended to establish geometric ergodicity in nonlinear autoregressions with conventional ARCH(q) errors.
Keywords: 330; Nichtlineares Verfahren; ARCH-Modell; Markovscher Prozess; Heteroskedastizität; Zeitreihenanalyse; Theorie